2008
DOI: 10.1177/039463200802100416
|View full text |Cite
|
Sign up to set email alerts
|

Acetylsalicylic Acid Inhibits Proliferation of Human Bone Marrow Stromal Cells and Matrix Mineralization

Abstract: Acetylsalicylic acid (ASA) and other non-steroidal anti-inflammatory drugs have been shown to potentially inhibit bone healing and bone formation in both animal and clinical studies. Due to the extensive diffusion of ASA-based long-term therapies, the implications of such a side-effect are of interest in all types of bone surgery, including bone grafting procedures and dental implant placement. In this study, we investigate the effect of ASA at therapeutic concentrations on the proliferation and osteogenic dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…None of these studies examined the effect of aspirin on bone healing within a dosing range equivalent to that commonly used in humans (<1 g per dose). The dose-dependent effect of aspirin on bone healing was also examined in an in vitro study 23 . That study showed aspirin to have a dose-dependent inhibitory effect on human bone-marrow stromal cell proliferation and matrix mineralization.…”
Section: T Here Was a Strong Relationship Between Mechanical Strengthmentioning
confidence: 99%
See 2 more Smart Citations
“…None of these studies examined the effect of aspirin on bone healing within a dosing range equivalent to that commonly used in humans (<1 g per dose). The dose-dependent effect of aspirin on bone healing was also examined in an in vitro study 23 . That study showed aspirin to have a dose-dependent inhibitory effect on human bone-marrow stromal cell proliferation and matrix mineralization.…”
Section: T Here Was a Strong Relationship Between Mechanical Strengthmentioning
confidence: 99%
“…Previous animal studies have shown aspirin to inhibit bone healing at high doses [19][20][21][22][23] . To our knowledge, our study is the first to demonstrate inhibition of bone healing by aspirin in an animal model within a dosing range equivalent to that typically employed in humans.…”
Section: T Here Was a Strong Relationship Between Mechanical Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Proliferation of BMSCs was determined using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay as previously described [41]. Briefly, 5 × 10 3 cells/well in 200 μL DMEM containing 10% fetal calf serum were inoculated into 96-well plates and cultured with medium containing various ODNs at a final concentration of 1 μg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…These cells are recruited and activated either by mast cellassociated chemotactic non-specific factors such as LTB4, PAF, the eosinophil chemotactic factor of anaphylaxis (ECF-A), and chemotactic specific factors: chemokines (44)(45)(46). These compounds also participate in the late phase reactions six hours subsequent to the exposure to the allergen (47).…”
mentioning
confidence: 99%